Increasing Knowledge Of Electric Hazards And Their Mitigation For Residents Of The Rw 15, Ciwaruga Village, Parongpong District, West Bandung - Siti Saodah; Achmad Mudawari; Ali Mashar; ahmad Deni; Aceng Daud; Erwin Yusuf; Teguh Sasono (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
Electricity is needed by the community because it is easily converted into other forms of energy. Electricity is very useful but at the same time dangerous for humans if they do not have the knowledge, understanding and skills about it. This training was carried out with the aim of providing knowledge about electrical hazards and skills in electrical installation for residents of RW 15, Ciwaruga Village, Parongpong District. With the materials and methods and approaches applied, the training can run smoothly and work well. This success is shown by the active participation and high enthusiasm of the participants during the training and the high level of absorption of the training materials delivered. This is reflected in the increase in knowledge and skills in terms of making good installations as indicated by the increase in the value of the final test results (posttest). In addition, this paper can also be used as a reference for parties who will carry out similar or other activities related to electrical installations.